KAJIAN HUKUM PENERAPAN FIKTIF NEGATIF DALAM HUKUM ADMINISTRASI NEGARA SEBAGAI KEPUTUSAN TATA USAHA NEGARA - Saindra Arafa Syam (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
AbstractPublic services are organized by the government or public service providers in terms of the petition filed by society, of course, expect to be met. But sometimes an application for a decree can not be met in terms of both requirements are not met nor of the procedural aspects of the old and long. One path taken apart complaint or objection submitted to the government, is through the legal system by submitting an application or a lawsuit at the Administrative Court of the State. Good application to obtain admission decision as provided for in Article 53 of Law No. 30 of 2014 on Government Administration and through lawsuits filed related to the refusal or decision fictitious negative as stipulated in Article 3 of Law No. 5 of 1986 concerning the State Administrative Cour., The resolution attempts through the courts is ultimium remudium (the last resort) for citizens to obtain the appropriate public service expected. Lawsuit or application to obtain the Decree of the Government would be expected to provide for community legal certainty, in addition as a correction for public servant in serving the community